Krüppel-like factor 4 promotes autophagy in macrophages under high glucose concentration by inhibiting the AKT/mTOR signaling pathway - Rui Zhang; Sisi Chen; Tongdan Wang; Pei Yu (Archive of Gerontology and Geriatrics Research - Peertechz Publications, 2023)
Background: Diabetic atherosclerosis (AS) is the main cause of disability and death in diabetes. In the progression of AS, autophagic activity plays an important role. Krüppel-like factor 4 (KLF4) is a member of the zinc finger protein transcription factor family and is believed to play a protective role in the pathogenesis of atherosclerosis. This study aimed to explore the role of KLF4 in diabetic atherosclerosis and the autophagic mechanism.  Methods: A diabetic mouse model was established and the expression level of KLF4 protein in the aorta of the mice was detected after a high-fat diet. The effects of KLF4 on cholesterol content, apoptosis, autophagy-related proteins, and the AKT/mTOR signaling pathway of THP-1 macrophages were also evaluated.  Results: The expression level of KLF4 protein in the aorta of diabetic mice was decreased. Meanwhile, overexpression of KLF4 in THP-1 macrophages significantly decreased cholesterol accumulation, increased beclin-1 expression, decreased P62 expression, enhanced LC3 fluorescence intensity decreased cell apoptosis and p-mTOR and p-AKT expression were decreased under the condition of high glucose. After the reduction of KLF4 expression, the result is reversed.  Conclusion: KLF4 induces autophagy by inhibiting the AKT/mTOR pathway and alleviates cholesterol deposition in THP-1 macrophages under high glucose concentration.